The Prostitution of Women - A Conscious Choice of a Life Path or Economic Duress - Małgorzata Henryka Kowalczyk (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2016)
Aetiology of indecent behaviours is a multidimensional issue. It is impossible to explain the conditions of prostitution while only referring to mono-causal concepts. In the previous traditional aetiological approaches, the simultaneous perspective is dominating and this emphasises the interrelated systems of factors found in educational environments and resulting from the economic conditions and cultural changes which modify the attitudes towards mores, sexuality and morals. However, the changing image of contemporary prostitution requires other factors determining this phenomenon and being found beyond the traditional areas of analysis. Considering the fact that prostitution connected with the dysfunctionality of family environments and authentic poverty is only incidental to the phenomenon, the research interests were focused on the sphere of human temperament and, especially, needs of stimulation. Objective and method: The main objective of the article was analysing different factors that could accompany the decision on practising prostitution and showing the possibilities of counteracting the phenomenon. In order to obtain a complete picture of a life situation, the selected elements of the personality profile and level of reactivity were discussed. The research used the method of browsing through secondary sources. Results: The article introduced three perspectives related to different approaches to the aetiology of prostitution. The first one refers to the traditional system of factors determining the phenomenon of prostitution that could be found in educational environments and cultural conditions. The multi-causal syndromes of factors determining prostitution mainly include the symptoms of family dysfunctionality, objective poverty or a subjective feeling of neediness, as well as the strongly stimulating, yet, in some cases, also depraving, influence of peer groups and the mass media promoting consumerism. The last category of factors may especially influence the attitudes and behaviours of young people accepting unlimited consumerism. That part of the article mentioned research results representing the multi-causal model. Among others, those were the studies of J. Kurzępa, M. Kowalczyk-Jamnicka, and J. Moczydłowska. The second discussed aetiological perspective refers to the psychosexual approach, which indicates the importance of specific personality traits and sexual experiences as the factors predestining women to practise prostitution. Followers of this perspective emphasise the independence of psychosexual factors of the changing social and economic conditions; therefore, these factors become universal. To support this approach, the research studies of J. Sztobryn-Giercuszkiewicz, J. Pabian and Z. Izdebski were mentioned. The psychosexual perspective emphasises the role of traumatic sexual experiences and the distorted personality traits of prostituting women; these factors can be correlated. The last presented approach was the stimulation perspective. This constitutes an aetiological alternative to the previous traditional perspectives. It emphasises that people have different demands for stimulation; therefore, some need strong stimuli which will maintain their excitement level on a high level. Some people are more inclined towards trying risky things, including prostitution. The stimulation perspective enables one to explain the reasons for practising prostitution by people who do not come from families with upbringing inefficiency, and material advantages obtained thanks to prostitution are not the only inspiring factor to them. The article ends with a discussion concerning possibilities of preventive measures which should take cultural and social changes into consideration and go beyond traditional patterns connected with reorganisation of dysfunctional environments.